2022
DOI: 10.3390/ani12243565
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Timing of Insemination at Spontaneous Estrus in Dairy Cattle

Abstract: Cows show spontaneous estrus over 8–20 h but become refractory to the bull about 10–12 h before ovulation. This indicates that ovulation occurs 10–12 h after the end of estrus behavior, yet spermatozoa from the bull ejaculate need to undergo maturation and capacitation for 6 to 8 h in the female reproductive tract before they are capable of fertilization. Traditionally, the onset of estrus has been considered the best timing for artificial insemination (AI) in cattle, that is, 6 to 24 h from the first signs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 78 publications
0
3
0
1
Order By: Relevance
“…Significant variations in the duration of estrus and the time interval between its onset, end, and the time of ovulation have been associated with the conception rate with sexed and CS in dairy cows [ 19 ]. A thorough exploration of the literature showed that the duration of estrus ranged from 7 to 16 h, and the onset and end of estrus to ovulation time ranged from 27 to 30 h and 12 to 19 h, respectively [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant variations in the duration of estrus and the time interval between its onset, end, and the time of ovulation have been associated with the conception rate with sexed and CS in dairy cows [ 19 ]. A thorough exploration of the literature showed that the duration of estrus ranged from 7 to 16 h, and the onset and end of estrus to ovulation time ranged from 27 to 30 h and 12 to 19 h, respectively [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The time interval between the onset/ or end of oestrus to the time of ovulation and the duration of oestrus varies widely in dairy cattle (López‐Gatius, 2022). In a study, it has been shown that the onset/and the end of oestrus to ovulation time and the duration of oestrus ranged from 27–30 h, 12–19 h and 7–16 h respectively (Dransfield et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Однако недавние результаты показывают, что этот интервал следует сократить до 16-6 часов до овуляции, приближая ее к концу течки. [15].…”
Section: классическая схемаunclassified